Social Media Content, Brand Image, and Price in Purchasing Decisions: Konten Media Sosial, Citra Merek, dan Harga dalam Keputusan Pembelian - Raffi, Muhammad; Komariah, Kokom; Saori, Sopyan (Indonesian Journal of Innovation Studies, 2025)
General background: The rapid evolution of digital technology and shifting consumer lifestyles due to globalization have intensified competition among businesses, especially in the food sector. Specific background: Bolu Amor, a local bakery brand in Sukabumi, faces fluctuating sales potentially influenced by the quality of its social media content, brand image, and price perception. Knowledge gap: Previous studies on purchase decisions often examined these variables in isolation or outside the food industry context, leaving a gap in integrated analyses within local bakery businesses. Aims: This study aims to analyze the simultaneous and partial effects of social media content, brand image, and price on consumer purchase decisions for Bolu Amor. Results: Based on a survey of 400 respondents and multiple linear regression analysis, all three variables significantly influenced purchase decisions, with price having the strongest effect. The model explains 8.4% of the variance in consumer decisions (R² = 0.084). Novelty: This research offers a comprehensive integration of digital and perceptual factors affecting purchase decisions in a local food brand, which remains underexplored in current literature. Implications: The findings provide strategic insights for improving digital marketing effectiveness and pricing strategies, guiding local businesses like Bolu Amor to align better with modern consumer behavior.Highlight : Price is the most dominant variable influencing consumer purchase decisions. Social media content, brand image, and price have a significant simultaneous effect. The three variables explain only 8.4% of the variation in purchase decisions. Keywords : Social Media Content, Brand Image, Price, Purchase Decision, Consumer